PENGGUNAAN MEDIA SOSIAL DAN KEPEKAAN SOSIAL SISWA DI SMA N 12 PEKANBARU - Satialisa Satialisa; Tri Umari; Elni Yakub (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The development of technology is inevitable and even the development of social media. 39% of the largest results in the survey, social media users are young people aged 16-21 years, not to mention among students also follow its development. So this study entitled